CITRA PEREMPUAN DALAM SAMPUL MAJALAH POPULAR PADA NO.310 EDISI NOVEMBER 2013 - Yohanna Amanda; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Women in the adult magazine, including popular magazine, held as an object sexual enjoyment. Sex approach appeall Each edition magazine describes as though they were women who want to sale of products Popular magazine. Various services that too much is revealed by the ends it is clear that attract the buyers. Image who describe will branding in their value of embraced of target market. it influence tobe gradation between hope and the reality and impacting to higest standart value of beauty adult women,Types of research that used writer in this research is qualitative interpretive. Technical data collection in document and an interview. Analysis techniques data will be done by using semiotics Roland Barthes significance to the theory two stages. Barthes makes a model that systematic in analyzing the meaning of a mark on the cover popular magazine edition no. 310 November 2013, which is the result of the construction reality that on the text, images that were found in home magazines Popular with using analysis of semiotics model Roland Barthes.The results of these studies show the meaning implicitly promoting women in cover Popular magazines edition 310 November 2013, the authors reviewing that at the cover of popular magazine using sexy women endorser is to abstract of modern women image as a part of her intim body is wanna shows as beauty image. And the result is the image that magazine show is looking like negative image because shows big boobs and leg as image tobe an aesthetismKata Kunci: citra perempuan, Semiotika, dan Analisis Simbol